PEMODELAN GEOSTATISTIKA DATA VERTICAL ELECTRICAL SOUNDING UNTUK MENENTUKAN DISTRIBUSI AKUIFER AIR TANAH (STUDI KASUS: INSTITUT TEKNOLOGI SUMATERA) - Aviv Alansyah (KURVATEK, 2021)
Geostatistical modeling is carried out to determine the spatial correlation of aquifer distribution with Vertical Electrical Sounding data. Geostatistical modeling is done using variogram analysis. Data Vertical Electrical Sounding used 24 point soundings using the Schlumberger configuration. The length of the VES measurement range is varied, with a minimum AB/2 of 2 m and a maximum AB/2 of 150 m and MN/2 changes made three times (0.5, 2, 10 m). VES data processing results are correlated with binding data in the form of Well Logging (resistivity log and SP logs). Based on the results of VES data processing and Well Logging, it was found that the ITERA campus has 2 aquifer layers, namely unconfined aquifers with resistivity values>80 μm which are suspected as tuff and confined aquifers with resistivity values of 20-80 80m which is thought to be the tuffaceous sandstone. In the geostatistical modeling, a model that is suitable for the distribution of VES data is obtained, which is a spherical variogram model with a 500 m lag. The results are used for gridding the iso resistivity map with kriging variogram correlated with the 3D model, it is obtained that the aquifer distribution in the western part is close to the surface (shallow) with a fairly thick layer that is around ± 48,865 m and increasingly towards the east the aquifer layer gets deeper and tend to thin out. Keyword : Aquifer, VES, Geostatistics, Well Logging, ITERA